IMPLEMENTASI CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS MULTIMEDIA INTERAKTIF DALAM PEMBELAJARAN IMAN KEPADA HARI AKHIR SEBAGAI UPAYA PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK KELAS IX A SMP NEGERI 2 TENGARAN - AMIN NURBAEDI (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2016)
The aim of this research is to determine the implementation Contextual Teaching and Learning (CTL) based on interactive multimedia, whether it can enhance the activity and learning outcomes in matter of faith in the final days. This research is a classroom action research which  is carried out in three cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. Data were collected using an achievement test, observation guidelines, field notes, and the records of learners. Data have been presented as percentages and analyzed using inductive, deductive, and comparative ways. Improvement in learning outcomes also occurred as evidenced by comparing the value at pre-action, the first cycle, second cycle and third cycle. In pre-action activities, the maximum score is 100; and also for the first, second, and third cycle. The achievement of a minimum value on pre-action activity continued to increase by 50 and 10 points to 60 in the first cycle, 70 in the second cycle, and 80 in the third cycle. The average value also increased significantly. On learning pre-action, the average value of only 84. In the second cycle increased to 90, on the second cycle and the third cycle increased to 92. The percentage of completeness increased from 77.42 on learning pre-action, turned into 87.10 in the second cycle, 96.77 in the second cycle, and 100 percent in the third cycle.